2012
DOI: 10.1016/j.chiabu.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Links between alcohol and other drug problems and maltreatment among adolescent girls: Perceived discrimination, ethnic identity, and ethnic orientation as moderators

Abstract: Objectives This study examined the links between maltreatment, posttraumatic stress symptoms, ethnicity-specific factors (i.e., perceived discrimination, ethnic identity, and ethnic orientation), and alcohol and/or other drug (AOD) problems among adolescent girls. Methods These relations were examined using archived data from a community sample of 168 Black and Hispanic adolescent girls who participated in a school-based substance use intervention. Results The results revealed that maltreatment was linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In mediational analyses, intervening variables were predominantly individual-level factors. For example, several studies found that racial/ethnic discrimination was associated with anger, post-traumatic stress symptoms, and depressive symptoms, which in turn were associated with alcohol abuse or dependence (Gray & Montgomery, 2012; Mulia & Zemore, 2012; Whitbeck, Chen, Hoyt, & Adams, 2004). As above, few studies examined mediators at social-ecological levels beyond the individual level.…”
Section: Resultsmentioning
confidence: 99%
“…In mediational analyses, intervening variables were predominantly individual-level factors. For example, several studies found that racial/ethnic discrimination was associated with anger, post-traumatic stress symptoms, and depressive symptoms, which in turn were associated with alcohol abuse or dependence (Gray & Montgomery, 2012; Mulia & Zemore, 2012; Whitbeck, Chen, Hoyt, & Adams, 2004). As above, few studies examined mediators at social-ecological levels beyond the individual level.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, intervention programs with Black youth have begun to incorporate aspects of positive RI to promote psychosocial development (see Jones & Neblett, 2016). Although not all studies of RI have demonstrated protective effects with regard to substance use (Gray & Montgomery, 2012), higher levels of RI are usually associated with more negative attitudes toward substances and less substance use (Brody et al, 2006; Pugh & Bry, 2007; Stock et al, 2013). For example, among FACHS adolescents, RI was associated with less affiliation with substance users, and, in turn, lower drug use willingness and substance use 5 years later (Stock et al, 2013).…”
Section: Racial Identity As a Protective Mechanismmentioning
confidence: 99%
“…Although there are many studies supporting the relationship between perceived discrimination and problem behaviors among adolescents, the researches mainly focus on the different racial groups (Acosta, Hospital, Graziano, Morris, & Wagner, 2015; Flores, Tschann, Dimas, Pasch, & De Groat, 2010; Gray & Montgomery, 2012). And besides, it need to be further explored that how the perceived discrimination affects problem behaviors.…”
Section: Discussionmentioning
confidence: 99%